EFEKTIFITAS TINDAKAN ORAL HYGIENE MENGGOSOK GIGI DENGAN PASTA GIGI YANG MENGANDUNG XYLITOL TERHADAP PH SALIVA PASIEN ICU DI BRSU TABANAN - Savitri, EMMY (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Oral physiology of patients will change within a few hours care in the ICU (Intensive  CareUnit).  Salivary pH of patients ICU may decrease. This condition can cause bacteria growing and  easier to produce acid.  This will speed up the process of demineralization of    tooth enamel,  causing dental caries,  and can lead to pneumonia. Brushing  teeth  can  increase  the  pH  of  saliva.  The  effect  of  xylitol  can  stimulates saliva  production,   alter  the  composition  of  saliva,  and    preventing  decrease  of salivary  pH.  This  study  aimed  to  determine  the  effectiveness  of  oral  hygiene toothbrushing  using  toothpaste  that  contains  xylitol  for  the  salivary  pH  patients   in ICU.  This  research  using  quasy  experimental  design  with  nonequivalent  control group  design.  Amount  of  sample  is  30  people  which  is  selected  using  purposive sampling  technique.  The  methode  to  collecting  sample  of  saliva  is  using  spitting method, and then the pH of saliva was measured by pH strips.  The results showed a difference  of  mean  of  salivary  pH  in  intervention  group  is  1.04  and  in  the  control group  is 0.773.  Statistical test results is using independent t-test and the result is  p<? (0,000  <0,05).  It  can  be  concluded  that  there  is  effectiveness  of  oral  hygiene  tooth brushing  using  toothpaste  that  contains  xylitol  for  salivary  pH  patients  in  general hospital Tabanan.
Keywords: Oral hygiene; tooth brush; xylitol; salivary ph